Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Literasi Sains Pada Tema Pencemaran Lingkungan (Universitas PGRI Sumatera Barat, 2022)
This article explains The Influence of Problem Based Learning Learning Models on Students' Scientific Literacy Ability on the Theme of Environmental Pollution